GERAKAN LITERASI SEKOLAH DALAM MENGEMBANGKAN KEMAMPUAN METAKOGNITIF PESERTA DIDIK DI SMP NEGERI 1 JAKARTA - Aziza, Luthfita; Sutisna, Anan; Margono, Gaguk (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This study aims to obtain in-depth information and empirical data on School Literacy Movement in developing the metacognitive ability of students in SMP Negeri 1 Jakarta. This research conducted from January to April 2018. The research method used is descriptive qualitative. The data collection used are observation, literature study, and in-depth interviews to the School Literacy Team, informants and key informants associated with the implementation of School Literacy Movement at SMP Negeri 1 Jakarta and expert opinion in accordance with the field of research that is members of the Task Force Literacy Schools at The Ministry of Education and Culture of the Republic of Indonesia. The results indicated that the School Literacy Movement in SMP Negeri 1 Jakarta was at the stage of habituation and not focused on the stage but on the continuous and stimulant activities. The development of metacognitive ability undertaken by SMP Negeri 1 Jakarta is by developing a strategy of literacy in the physical environment, social-affective, academic, and familiarize the students to literate using HOTS (Higher Order Thinking Skill). In addition, there are three aspect of metacognitive ability of students in SMP Negeri 1 Jakarta, there are characteristics of strategy, task characteristics, and characteristics of people that can be seen through various ways such as the process of asking questions, related to real life situation, students' knowledge of the conditions that will facilitate or inhibits itself in solving problems faced and switch to using different learning strategies if it has not succeeded, and understood the students against the shortcomings and advantages themselves and that existed in other students. In addition, after the implementation of the School Literacy Movement there is a change of habits demonstrated by students and the change is at the metacognitive stage as it aims to improve the practice (inquiry into inquiry).